Optimising the care for older persons with complex chronic conditions in home care and nursing homes: design and protocol of I-CARE4OLD, an observational study using real-world data - Hoogendijk, Emiel O; Onder, Graziano; Smalbil, Louk; Vetrano, Davide L; Hirdes, John P; Howard, Elizabeth P; Morris, John N; Fialová, Daniela; Szczerbińska, Katarzyna; Kooijmans, Eline Cm; Hoogendoorn, Mark; Declercq, Anja; et al. (BMJ open, 2023)
INTRODUCTION: In ageing societies, the number of older adults with complex chronic conditions (CCCs) is rapidly increasing. Care for older persons with CCCs is challenging, due to interactions between multiple conditions and their treatments. In home care and nursing homes, where most older persons with CCCs receive care, professionals often lack appropriate decision support suitable and sufficient to address the medical and functional complexity of persons with CCCs. This EU-funded project aims to develop decision support systems using high-quality, internationally standardised, routine care data to support better prognostication of health trajectories and treatment impact among older persons with CCCs. METHODS AND ANALYSIS: Real-world data from older persons aged ≥60 years in home care and nursing homes, based on routinely performed comprehensive geriatric assessments using interRAI systems collected in the past 20 years, will be linked with administrative repositories on mortality and care use. These include potentially up to 51 million care recipients from eight countries: Italy, the Netherlands, Finland, Belgium, Canada, USA, Hong Kong and New Zealand. Prognostic algorithms will be developed and validated to better predict various health outcomes. In addition, the modifying impact of pharmacological and non-pharmacological interventions will be examined. A variety of analytical methods will be used, including techniques from the field of artificial intelligence such as machine learning. Based on the results, decision support tools will be developed and pilot tested among health professionals working in home care and nursing homes. ETHICS AND DISSEMINATION: The study was approved by authorised medical ethical committees in each of the participating countries, and will comply with both local and EU legislation. Study findings will be shared with relevant stakeholders, including publications in peer-reviewed journals and presentations at national and international meetings.
Keywords: Aging; algoritmy; Home Care Services; chronická nemoc; Humans; lidé; senioři nad 80 let; senioři; umělá inteligence; Observational Studies as Topic; pozorovací studie jako téma; Aged; Algorithms; Artificial Intelligence; Chronic Disease; Aged, 80 and over; stárnutí; služby domácí péče